2013
DOI: 10.1002/icd.1826
|View full text |Cite
|
Sign up to set email alerts
|

Children's Attitudes towards Peers with Disabilities: Associations with Personal and Parental Factors

Abstract: The purpose of this study was to investigate the following: (i) associations among children's prior contact with people with disabilities and the three dimensions of children's attitudes towards people with disabilities: children's understanding of and their feelings about people with disabilities and their behavioural intentions to make inclusion decisions; (ii) the relation between children's behavioural intentions to make inclusion decisions and the demands of activity contexts and the types of disabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 40 publications
6
52
0
7
Order By: Relevance
“…This underlines the importance of parental behaviour as role models for children’s self‐efficacy beliefs and their attitudes. Our results are widely consistent with the current state of research (for example, de Boer et al, ; Innes & Diamond, ; Katz & Chamiel, ), even though there are findings that do not support Feinman’s () theory of social referencing (de Boer et al, ; Hong et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This underlines the importance of parental behaviour as role models for children’s self‐efficacy beliefs and their attitudes. Our results are widely consistent with the current state of research (for example, de Boer et al, ; Innes & Diamond, ; Katz & Chamiel, ), even though there are findings that do not support Feinman’s () theory of social referencing (de Boer et al, ; Hong et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…In the literature review by de Boer et al (), no effects of parents’ attitudes towards inclusive education and the social participation of students with special educational needs were found. In a recent study conducted by Hong et al (), the authors could not provide evidence for a relationship between children’s and parents’ attitudes towards children with disabilities.…”
Section: Children’s Attitudes Towards Peers With Learning Disabilitiementioning
confidence: 89%
See 1 more Smart Citation
“…Louis et al, 2008). The selection of obesity and wheelchair as anchor traits is based on a body of literature identifying those conditions as being recognizable among children (e.g., Bell & Morgan, 2000;Hong, Kwon, & Jeon, 2014). Stuttering video.…”
Section: Instrument Characteristicsmentioning
confidence: 99%
“…They were also required to write down the type of disability of their schoolmate. Hong, Kwon and Jeon (2014) found that the development of children's attitudes towards disability is positively influenced by the experience of personal encounter with people with disabilities, regardless of their structure.…”
Section: Diagram the Average Of The Correctly Named Categories By Thementioning
confidence: 96%